Magnetoelectric nanoparticles shape modulates their electrical output - Marrella, A.; Suarato, G.; Fiocchi, S.; Chiaramello, E.; Bonato, M.; Parazzini, M.; Ravazzani, P. (Frontiers in Bioengineering and Biotechnology, 2023)
Core-shell magnetoelectric nanoparticles (MENPs) have recently gained popularity thanks to their capability in inducing a local electric polarization upon an applied magnetic field and vice versa. This work estimates the magnetoelectrical behavior, in terms of magnetoelectric coupling coefficient (αME), via finite element analysis of MENPs with different shapes under either static (DC bias) and time-variant (AC bias) external magnetic fields. With this approach, the dependence of the magnetoelectrical performance on the MENPs geometrical features can be directly derived. Results show that MENPs with a more elongated morphology exhibits a superior αME if compared with spherical nanoparticles of similar volume, under both stimulation conditions analyzed. This response is due to the presence of a larger surface area at the interface between the magnetostrictive core and piezoelectric shell, and to the MENP geometrical orientation along the direction of the magnetic field. These findings pave a new way for the design of novel high-aspect ratio magnetic nanostructures with an improved magnetoelectric behaviour.